Production of Lemongrass Extract to Control the Stink Bugs (Leptocorisa acuta L.) in Babatan Village, Lintang Kanan District - Haperidah Nunilahwati; Yani Purwanti; Neni Marlina; Suyitno Suyitno; Fitri Yetty Zairani; Burlian Hasani; Marlina Marlina (Altifani Journal: International Journal of Community Engagement, 2023)
The use of chemical pesticides in controlling pests is still widely used by some farming communities in Babatan Village, Lintang Kanan District, Empat Lawang Regency. Improved use of chemical pesticides hurts agricultural production and the environment. One alternative to chemical pesticides is plant-based pesticides which are safer and more environmentally friendly in supporting the implementation of integrated pest control (IPM). The results of a field survey in Babatan Village show that many plants can be used as vegetable pesticides, such as citronella (Cymbopogon sp) as a substitute for chemical pesticides. This counseling activity aims to introduce the benefits and methods of making lemongrass extract to control the pest stink bugs (Leptocorisa acuta L.) which attack many rice plants in Babatan Village. Implementation of activities on 4-5 February 2022 with the target targeting members of the Makmur Jaya Farmer Group. This community service activity uses counseling methods (lectures and discussions), demonstrations, and evaluations. The results of this activity indicate that the members of the Makmur Jaya Farmer Group, Babatan Village, Lintang Kanan District, Empat Lawang Regency gave a good response, can understand, and will apply the method of making and using the lemon grass plant pesticide in suppressing the stink bugs pest population so that the cost of buying chemical pesticides can be reduced, produce healthy plants, no residue that pollutes the product and the environment, and sustainably increases production.